Pengaruh Model Pembelajaran Outdoor Education Terhadap Kecerdasan Emosional Siswa - Latansa, Khamdu; Hudah, Maftukin; Maliki, Osa (Jurnal Sporta Saintika, 2025)
Outdoor Education demands student participation in adventurous challenges. Some examples of outdoor activities are hiking, rock climbing, camping, fishing, survival, caving, beachcombing, exploring, cooking, gardening, rice planting, and others. Emotional intelligence is the ability to motivate oneself and persevere in the face of frustration, control impulses and not exaggerate pleasure, regulate moods, and ensure that stress does not get in the way of thinking, empathizing, and praying. This study aims to determine the development of students' emotional intelligence through the application of outdoor education learning models. This study uses a quantitative method with an experimental approach Pre-test and Post-test control group design then the research design used in this study is True experimental Design. In this design there are two groups. The first group is the experimental class that is given treatment (X) and the second group is the control class that is not given treatment. the average value of the control class is 109.13 and the experimental class is 115.75. The average score of the control class was lower than the experimental class. The experimental group proved better and developed students' emotional intelligence in physical education. Then in the hypothesis test results obtained sig. (2-tailed) the result is 0.015, meaning that the sig. (2-tailed) value is smaller than 0.05, so Ho is rejected and Ha is accepted